Facies analysis and chemostratigraphy of the Chattanooga Formation in Tenneesee and Alabama - Eme, Chinyere Eunice (Kansas State University, 2023)
The black shales of the Late Devonian to Early Mississippian are known for their rich organic concentrations, serving as source rock and housing unconventional reservoirs. The primary driving mechanism for the high organic matter content of these mudstones is yet to be fully understood. Interpretation of the complex factors controlling deposition of these mudrocks is facilitated by an integration of sedimentologic and chemostratigraphic analysis. Facies analysis, coupled with hand-held X-ray fluorescence (HHXRF), inductively-coupled plasma mass spectrometry (ICP-MS), X-ray diffraction (XRD), tipping point and total organic carbon (TOC) analyses were performed to construct sedimentologic-chemostratigraphic logs that allowed the establishment of a stratigraphic framework, and evaluation of depositional parameters such as detrital input, primary productivity, and degree of oxygenation during the accumulation of the studied succession. The ultimate goal was to identify the controls on sedimentation and main switches in organic matter content of the Chattanooga Formation (Devonian of the Appalachian Basin) in outcrops in Tennessee (TN-1) and Alabama (AL-1). The facies associations indicate that these successions were deposited in deep-marine environments varying from hemipelagic-lower shoreface to pelagic settings. Three sequences were identified in the sedimentary successions at each location (sequences 1 through 3, from base to top). The succession at TN-1 shows an oxic to anoxic environment of deposition with TOC values increasing upward from 3.49-17.80 wt%, while AL-1 shows an anoxic to oxic depositional environment from base to the top of the succession, with decreasing TOC values from 13.3-5.32 wt%. The stratigraphic framework shows incomplete system tracts, which can be attributed to poor preservation of the sedimentary succession resulting from low subsidence rates, typical of epicontinental basins. The only complete sequence, with lowstand, transgressive and highstand system tracts, is sequence 1 at AL-1. The integration between sedimentological data and chemical indices suggests that high organic content (TOC>10%) is found in settings where high primary productivity coincides with bottom-water anoxia.
Keywords: Sedimentology; Chemostratigraphy; Sequence stratigraphy; Facies analysis; Depositional environment